Counterfeiting Shakespeare : evidence, authorship, and John Ford's Funerall elegye - Vickers, Brian (Cambridge University Press, 2002)
Brian Vickers examines the issue of what Shakespeare actually wrote, and how this is determined. Shakespeare's authorship has been claimed for two poems, 'Shall I die?' and A Funerall Elegye. Vickers shows that neither has the requisite stylistic and imaginative qualities. In other words, they are 'counterfeits', in the sense of anonymously authored works wrongly presented as Shakespeare's. He identifies John Ford as author of the Elegye.